1999
DOI: 10.1007/bf02465325
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic plasticity in the hippocampus during afferent activation reproducing the pattern of the theta rhythm (theta plasticity)

Abstract: This review summarizes data on the plasticity of hippocampal synaptic pathways in conditions of afferent activation modeling the electrical activity of neurons during the theta rhythm. Activation with short trains of stimuli with frequencies of about 5 Hz efficiently induces long-term potentiation, i.e., stable facilitation of synaptic transmission. Contrarily, single stimuli presented at the same frequency "depotentiate" synapses or even induce long-term depression. Combined theta activity at two synaptic inp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 70 publications
0
5
0
Order By: Relevance
“…Input frequencies in hippocampal networks are determined in large part by population oscillatory events. Theta (4–12 Hz) oscillations are present in local field potential recordings collected from the hippocampus of adult animals while they explore and solve mazes and have been shown to have a role in synaptic plasticity ( Kleshchevnikov, 1999 ) and learning and memory ( Buzsáki, 2005 , Hasselmo and Stern, 2014 ). Stimulation patterns set to mimic APs riding on an endogenous theta wave, i.e.…”
Section: Late Postnatal Changes In Network Oscillations and Excitabilmentioning
confidence: 99%
See 1 more Smart Citation
“…Input frequencies in hippocampal networks are determined in large part by population oscillatory events. Theta (4–12 Hz) oscillations are present in local field potential recordings collected from the hippocampus of adult animals while they explore and solve mazes and have been shown to have a role in synaptic plasticity ( Kleshchevnikov, 1999 ) and learning and memory ( Buzsáki, 2005 , Hasselmo and Stern, 2014 ). Stimulation patterns set to mimic APs riding on an endogenous theta wave, i.e.…”
Section: Late Postnatal Changes In Network Oscillations and Excitabilmentioning
confidence: 99%
“…Theta power is reduced relative to more mature animals and CA1 pyramidal neurons do not burst. The result is an increased proclivity to induce LTD during bouts of theta ( Kleshchevnikov, 1999 ). (C) An illustration of a filtered EEG trace recorded in area CA1 of the hippocampus at 30 days of age.…”
Section: Developmental Changes In Metaplasticity Align With Hippocampmentioning
confidence: 99%
“…In the present study we found a decrease in mechanical threshold and increase in number of action potentials produced by threshold and suprathreshold stimulation in rats consuming alcohol, but not in ddC-treated rats. The increase in number of short ISIs, in response to both threshold and suprathreshold mechanical stimulation, in alcohol fed rats, will increase temporal summation in postsynaptic spinal dorsal horn neurons; increasing the range of ISIs, near 100 ms, as observed in rats consuming alcohol, causes greater temporal summation of C-fiber-evoked excitatory postsynaptic currents in dorsal horn neurons [35], and in the same range of ISIs, temporal summation of afferent activity appears to be an important factor in human pain perception [3641].…”
Section: Discussionmentioning
confidence: 99%
“…We would add to this discussion the idea that novelty-or stress-induced depotentiation and LTD reflect active memory reversal processes, which can involve CaMKII, NCAM and cytokine actions (discussed above), as well as activation of b-adrenergic receptors, the amygdala (Katsuki et al, 1997;Nakao et al, 2004), and glutamate (NMDA) receptor activity (Nicoll et al, 1998;Kemp et al, 2000;Mockett et al, 2002;Villarreal et al, 2002;Daoudal and Debanne, 2003;Kosub et al, 2005). The depotentiation process, which can be triggered by exploration-related (theta) activity (Staubli and Lynch, 1990;Larson et al, 1993;Staubli and Chun, 1996;Holscher et al, 1997;Scafidi, 1997, 1999;Kleshchevnikov, 1999;Hyman et al, 2003), would reverse hippocampal plasticity that had been induced by recent learning experiences. This process is adaptive because when previously induced plasticity is ''reset'' to a depotentiated state by exploration, novelty, or a stressful experience, the hippocampus can then generate a representation of the new experience via the induction of endogenous LTP on a ''refreshed'' or ''uncluttered'' baseline state of plasticity.…”
Section: Does Stress Induce An Endogenous Form Of Ltd/depotentiation?mentioning
confidence: 94%